Revealing the Implementation of Government Accounting Standards in Village Fund Management - Gema Sri Basyir (Cita konsultindo, 2024)
This study aims to explain and provide an overview of the application of village fund accounting in the Mambalan village government. The research paradigm used is interpretive and phenomenological as a research method. The types of data collected in this study are primary data and secondary data. Data collection techniques in the form of interviews and documentation. The data that has been collected is then analyzed using noema, epoche, noesis, intentional analysis, and eidetic reduction. The results of this study reveal that the application of village fund accounting in the Mambalan Village Government based on the awareness of the Village Secretary is in accordance with the applicable Government Accounting Standards and refers to local government regulations. The Village Secretary as the accounting recorder is required to have extensive knowledge of Government Accounting Standards and applicable regulations so that the application of accounting can run properly and correctly. The implication of this research is that village officials must have a good and correct understanding of the applicable regulations, especially regarding financial recording so that village government operational activities can run smoothly. Keywords: village fund accounting, single entry, accrual basis